Exploring the Role of Medicinal Plant-Based Immunomodulators for Effective Therapy of Leishmaniasis - Chouhan, Garima; Islamuddin, Mohammad; Sahal, Dinkar; Afrin, Farhat (Frontiers in Immunology, 2014)
Leishmaniasis is a pestilent affliction that importunately needs better therapeutics necessitated by absence of effective vaccine, emergence as HIV co-infection and the dread of debilitating chemotherapy. The Leishmania parasites incapacitate host macrophages by preventing the formation of phagolysosomes, impeding antigen presentation to T cells, leading to suppression of cell-mediated immunity. An ideal approach to cure leishmaniasis includes administration of antileishmanial compounds that can concomitantly establish an effective Th1 response via restoration of requisite signaling between macrophages and T cells, for subsequent activation of macrophages to eliminate intracellular amastigotes. Plants have provided an opulent treasure of biomolecules that have fuelled the discovery of antileishmanial drugs. Modulation of immune functions using medicinal plants and their products has emerged as an effective therapeutic strategy. Herein, we review the plant extracts and natural products that have resulted in therapeutic polarization of host immunity to cure leishmaniasis. These immunostimulatory phytochemicals as source of potential antileishmanials may provide new strategies to combat leishmaniasis, alone or as adjunct modality.